Iron-catalyzed regioselective C-H alkylation of indoles: an additive-free approach in renewable solvent - Pradhan, Chandini; Jagtap, Rahul A.; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Punji, Benudhar (Green Chemistry, 2023)
Alkylated indoles are important motifs in various biologically active molecules and drug candidates. Herein, we report a mild and efficient iron-catalyzed protocol for synthesizing alkylated indoles via C-H bond alkylation of indoles with unactivated alkenes, demonstrating a high level of regioselectivity. The reaction occurs under additive-free, solvent-free (or trace green solvent, 2-MeTHF) and less energy-intensive conditions using a sustainable metal catalyst and provides easy access to privileged alkylated indoles with anti-Markovnikov selectivity. Alkylation is compatible with important functionalities, such as fluoro, chloro, trifluoromethyl, alkenyl, ether, thioether, silyl, and siloxane, including heteroaryl, pyridinyl, carbazolyl, and indolyl moieties (45 examples, up to 96% yield). The developed protocol is very simple, straightforward, and fully accords with the principles of green chemistry. A detailed mechanistic investigation manifests the facile indole's C-H activation at the Fe(0) center, reversible 1,2-insertion of the alkene into the Fe-H bond of a metallacycle, and a turnover-limiting reductive elimination. Alkylated indoles are important motifs in various biologically active molecules and drug candidates.
Keywords: Aromatic Ketones; Green; organic synthesis

Iron-catalyzed C-C and C-N bond-forming tandem amidation offering access to 3-amino-3-aminomethyl-2-oxindole frameworks - Ankade, Shidheshwar B.; Pradhan, Chandini; Samal, Pragnya Paramita; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
An iron-catalyzed protocol for the synthesis of 3-amino-3-aminomethyl-2-oxindole heterocyclic structures is disclosed employing isatins and non-nucleophilic N-methoxybenzamides. This reaction class is associated with broad scope and tolerates numerous functionalities, such as fluoro, chloro, bromo, iodo, trifluoromethyl, nitrile, ester, ether, and alkenyl, including heteroaryl - thiophene, benzothiophene, carbazolyl, indolyl, eugenol, and polycyclic cholesterol moieties. Detailed mechanistic investigations reveal that the reaction proceeds via iron-catalyzed N-O bond cleavage in N-methoxybenzamides, generating formaldehyde and benzamide, and through the intermediacy of isatin-ketimines and N-(hydroxymethyl)benzamides. Overall, this amidation reaction involves one C-C and two C-N bond-forming tandem processes, providing a range of beta-amino-aminomethyl-oxindoles (45 examples) in up to 88% yields. image
Keywords: benzamide; iron; Isatin; tandem amidation; tetrasubstituted carbon stereocenter